Students’ Opinion of Reading English Subtitle of Korean Drama on Vocabulary Enhancement - Chusna, Anggya Dewi (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2025)
Vocabulary acquisition is an important component of language learning, as a larger vocabulary enhances fluency in a foreign language. While traditional reading materials like books matters for vocabulary development, other media sources such as subtitles can also play a significant role. This research aims to analyze students’ opinions on the effectiveness of reading English subtitles in Korean dramas for vocabulary enhancement. The study employs a qualitative descriptive design, with data presented in simple tables accompanied by explanations. Data collection was conducted through an online questionnaire and interviews, and instrument validation was performed using expert judgment. The research participants included 101 students from IAIN Kediri, representing students from the 2017, 2018, 2019, and 2020 cohorts, with 6 students selected for interviews. The findings reveal the following: (1) A majority of students (76.2%) expressed high agreement with the experience of using subtitles as a learning tool. (2) A significant percentage (77.2%) agreed on the benefits of subtitles for vocabulary enhancement. (3) The students’ opinions on the impact of subtitles on vocabulary implementation and awareness also showed high agreement (72.5%). Overall, the average of the three indicators was 75.3%. These results suggest that English subtitles in Korean dramas can be an effective tool for vocabulary enhancement. The findings highlight the potential of using media such as subtitles to bridge entertainment with language learning.